2017
DOI: 10.11114/ijsss.v5i10.2657
|View full text |Cite
|
Sign up to set email alerts
|

Freeing Leonardo da Vinci’s Fight for the Standard in the Hall of the Five Hundred at Florence’s Palazzo Vecchio

Abstract: Beyond previous hypotheses, the author envisions here that, after drilling a 1/2-inch hole at 0.915 meters from the floor, on the vertical line that leaves the virtual larynx of the screaming supine soldier in the Battle of Marciano, a laparoscope will point at the virtual larynx of the yelling prostrate soldier in the Fight for the Standard. Our wild assault against the wild and against humanistic intelligence is unsustainable. From a humanistic standpoint, the quantum-computing search to see again the classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In the summer of 1996, I examined 18 subjects in the Boston Higashi School at Randolph (MA, USA) with the help of Helen Tager-Flusberg (then at the University of Massachusetts) and Alfonso Caramazza of Harvard University (Cassella, 1997). Three years later, my doctoral research at UNESR (Universidad Nacional Experimental Simón Rodrí guez) in Venezuela over Jean Piaget"s findings and the rise of polyvalent discourse in preschoolers, under the guidance of José Padrón (Cassella, 2000), confirmed my hypothesis (Cassella, 1997(Cassella, , 2000(Cassella, , 2017b(Cassella, , 2018c) that creative intelligence balances two domains of cognition: "spacetime" and "hyperspace" (Caramazza, 1994)…”
Section: The Research Supporting the Logos Heuristicsmentioning
confidence: 62%
See 1 more Smart Citation
“…In the summer of 1996, I examined 18 subjects in the Boston Higashi School at Randolph (MA, USA) with the help of Helen Tager-Flusberg (then at the University of Massachusetts) and Alfonso Caramazza of Harvard University (Cassella, 1997). Three years later, my doctoral research at UNESR (Universidad Nacional Experimental Simón Rodrí guez) in Venezuela over Jean Piaget"s findings and the rise of polyvalent discourse in preschoolers, under the guidance of José Padrón (Cassella, 2000), confirmed my hypothesis (Cassella, 1997(Cassella, , 2000(Cassella, , 2017b(Cassella, , 2018c) that creative intelligence balances two domains of cognition: "spacetime" and "hyperspace" (Caramazza, 1994)…”
Section: The Research Supporting the Logos Heuristicsmentioning
confidence: 62%
“…At this point, we should worry about the effect of disintegrating crystals of methane clathrates (Cassella, 2017a(Cassella, , 2017b(Cassella, , 2018c2018d;2018f) on the bottom of our seas, the consequent loss of the marine interface that separates oxygen-fed from sulphur-fed bacteria, the destruction of the ozone layer (Ward, 2006) by the release of hydrogen-sulfide gas, and the end of civilization as we know it.…”
Section: The Destructive Effects Of Technical Evolution and Social Inmentioning
confidence: 99%
“…within the second attention, our curious facet (which autistics cannot fathom) places between parentheses a known belief and goes to the edge of madness in order to seize the darkness of imaginary numbers, discourse pragmatics, and personal pronouns; finally, My latest research (Cassella, 2017g) found that the Third Attention sustains our vein of humanistic creativity and our smiles at puns lodged in the crossing of opposite beliefs. In my view (Cassella, 2016), our Stone-Age ancestors knew that the Third Attention redirects the power of our second attention to place between parentheses the repetitive truths guarded by our autistic first attention.…”
Section: Introductionmentioning
confidence: 98%
“…I added later (Cassella, 2002) an expression of the cognitive principles behind the 1 st attention spared in autism and the principles of the 2 nd attention damaged in the autistic brain. Within the logos heuristics (Cassella, 2002(Cassella, , 2008(Cassella, , 2011(Cassella, , 2014(Cassella, , 2017a(Cassella, , 2017b(Cassella, , 2018a(Cassella, , 2018b(Cassella, , 2018c(Cassella, , 2018d, I posited that the 1 st attention in the autistic spacetime of the crystal Thummim follows the principles that a) no object can exist in two or more places simultaneously (Locality); and that two or more objects cannot share the same space at the same time (Impenetrability).…”
Section: Introductionmentioning
confidence: 99%